MOLECULAR DIAGNOSIS OF ERYSIPELAS DUE OPPORTUNISTIC BACTERIA OF THE GENUS STAPHYLOCOCCUS IN SURGICAL PRACTICE - A. G. Khasanov; A. R. Mavzyutov; D. G. Shaibakov; A. A. Khaliullina (Креативная хирургия и онкология, 2017)
A molecular  genetic  study  of skin biopsy specimens using the  PCR reaction has done. Investigation of  strains  of  S.aureus, flakes  of  skin epidermis  with inflammatory foci and congruent with the healthy part of erysipelas in patients revealed the most common genetic markers  of pathogenicity factors of staphylococci.